Open Economy Public Finance - David E. Wildasin (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Many important questions in the field of public finance can be viewed as problems involving public policies in open economies. This paper draws together, from that perspective, a wide range of topics in public economics, emphasizing the implications of resource mobility for our understanding of the efficiency and distributional impacts of public policies. These topics are relevant for the purposes of policy evaluation, political economy, and the broadest questions of governance and of public sector organization at all levels of government, from the purely local to the global.
Keywords: H00; R00; F20; F60; J20; J60; 330; tax incidence; redistribution; social insurance; subnational governments; international; fiscal competition; urban